Public administration for planners : leadership and responsibility in theory and practice - Kehs, Stephen, 4 0 16; 5 (New York, NY : Routledge, 2023)
This book offers an introduction to public administration by a veteran practitioner, written for planners, as well as students seeking a public administration career and individuals simply wanting to learn more about responsible government. The narrative provides an overview of public administration theory and the importance of leadership in today's contentious political environment. The book contains five broad sections including an introduction, sections on management, the public sector, government programs, and some impressions on why this subject is so critically important in our society today. Typical administrative responsibilities are addressed as well as issues not typically covered in books on public administration, along with observations about sound public administration. Each section also contains practical exercises
Keywords: 2 -- 0; 6; United States.;Planning. -- Public administration;Public administration -- United States; 20; 2